Family Support in Management of Lactation Management in Mother With Children During Pandemic Covid-19 - Rimawati, Rimawati; Suwardianto, Heru (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Research Design using Cross-Sectional Design. The population is all mothers with infants in the Pesantren District of Kediri City using the incidental sampling technique, with a sample of 30 respondents. The Independent variable is Family Social Support and the Dependent variable is Lactation Management. The instrument uses a questionnaire. Statistical tests using the spearmen rho The results showed that the most supportive assessment of family support was as good as 18 respondents (60%), Instrumental Support was mostly as good as 18 respondents (60%), the most information support was good as many as 15 respondents (50 %) The most emotional support is good as many as 15 respondents (50%). The results of the study using the Rho spearman test obtained p = 0.025 with a Correlation Coefficient of 0.612 which means there is a strong relationship between family support and lactation management.